Recent advances in biomass phytic acid flame retardants - Liu, Yi; Zhang, Anshen; Cheng, Yamin; Li, Menghua; Cui, Yuanchen; Li, Zhiwei (Polymer testing, 2023)
With the rapid growth of industrialization, polymers have become widely used in people's daily lives. However, the flammability of these materials poses a potential threat to people's safety and property. To support sustainable development, it is important and urgent to develop high-performance, green flame retardants. One such material that has garnered significant attention in the flame-retardant field is biomass phytic acid, which has high phosphorus content and excellent biocompatibility. In this review, we focus on the use of phytic acid in plastics, fabrics, and other polymers for fire resistance, including its intrinsic flame-retardant properties, phytate metal, phytate ammonium and multicomponent compounds. We also discuss the proposed mechanisms behind these flame-retardant properties and explore future trends in the field. [Display omitted] •Recent advances of phytic acid and its derivatives as flame retardants are discussed.•Its classification, flame retardancy, and mechanism are introduced in detail.•Future developments of phytic acid-based flame retardants are discussed.